Murine Typhus Presenting With Mucosal Involvement. (3rd December 2020) - Rees, Renuka; Park, Christine; Long, Benjamin; Spencer, Steven; Sutter, Deena
Abstract: Lipschutz ulcers (LU) present as painful genital ulcers in nonsexually active females. Associated infections include Epstein Barr virus, Mycoplasma pneumoniae, Cytomegalovirus, and influenza. To our knowledge, this is the first report of LU occurring with murine typhus. Murine typhus is caused by Rickettsia typhi, a Gram-negative, obligate intracellular organism. Rat fleas ( Xenopsylla cheopis ) are the classic vector, although cat fleas ( Ctenocephalides felis ) found on cats, dogs, and opossums have been implicated in maintaining the life cycle of R. typhi in suburban areas. Murine typhus can have a nonspecific presentation making a strong index of suspicion crucial to its diagnosis. The most common presenting signs include fever, poor appetite, malaise, and headache. Laboratory abnormalities may include elevated C-reactive protein, elevated erythrocyte sedimentation rate, hypoalbuminemia, elevated transaminases, elevated neutrophil band count, and thrombocytopenia. The treatment of choice for R. typhi is doxycycline. Abstract : Lipschutz ulcers (LU) present as painful genital ulcers in nonsexually active females. To our knowledge, this is the first report of LU occurring with murine typhus.